Le pouvoir impérial dans les provinces syrienne s représentations et célébrations d'Auguste à Constantin (31 av. J.-C.-337 ap. J.-C.) - Bru, Hadrien. (Culture and History of the Ancient Near East, 2011)
This book focuses on the role of the emperor and the image of the Roman Empire as a whole during the time period from Augustus to Constantine. It analyses this image by taking into account the epigraphic, literary, numismatic and archaeological sources from Phoenicia to Osrhoene and from Commagene to Arabia. While discussing Graeco-Roman cities and rural settlements among desert areas, it addresses celebrations as well as the organization and promotion of the imperial cult in the Near East. This includes the imperial cult's forms of expression of symbolic, political, and various other social or religious functions. This approach, therefore, explores the real and imaginary relationships that existed between the Roman Empire and the populations of the Syrian provinces.